Acetabular changes associated with avascular necrosis of the femoral head in a piglet model. Issue 4 (April 2014) - Shapiro, F.; Connolly, S.; Zurakowski, D.; Flynn, E.; Jaramillo, D.
Abstract : Objectives: An experimental piglet model induces avascular necrosis (AVN) and deformation of the femoral head but its secondary effects on the developing acetabulum have not been studied. The aim of this study was to assess the development of secondary acetabular deformation following femoral head ischemia. Methods: Intracapsular circumferential ligation at the base of the femoral neck and sectioning of the ligamentum teres were performed in three week old piglets. MRI was then used for qualitative and quantitative studies of the acetabula in operated and non-operated hips in eight piglets from 48 hours to eight weeks post-surgery. Specimen photographs and histological sections of the acetabula were done at the end of the study. Results: The operated-side acetabula were wider, shallower and misshapen, with flattened labral edges. At eight weeks, increased acetabular cartilage thickness characterised the operated sides compared with non-operated sides (p < 0.001, ANOVA). The mean acetabular width on the operated side was increased (p = 0.015) while acetabular depth was decreased anteriorly (p = 0.007) and posteriorly (p = 0.44). The cartilage was thicker, with delayed acetabular bone formation, and showed increased vascularisation with fibrosis laterally and focal degenerative changes involving chondrocyte hypocellularity, chondrocyte cloning, peripheral pannus formation and surface fibrillation. Conclusions: We demonstrate that femoral head AVN in the young growing piglet also induced, and was coupled with, secondary malformation in acetabular shape affecting both articular and adjacent pelvic cartilage structure, and acetabular bone. The femoral head model inducing AVN can also be applied to studies of acetabular maldevelopment, which is less well understood in terms of developing hip malformation. Cite this article: Bone Joint Res 2014;3:130–8.